An Experience of Microbiological Data Sharing - Giacomini, M.; Nappo, A. (Methods of Information in Medicine, 2006)
Objectives: The control of infections and their resistance to antibiotics in hospitals is a matter of vital importance in the follow-up of transplant patients. This project has the purpose of translating microbiological reports from an obsolete file structure to a system which could guarantee a more correct and quick transmission of data, a system of storage which reduces the possibility of errors, a smoother manipulation, consultation and updating of data and, at least, a simple way to compute the cost of analysis, based on the costs determined by the national’s DRG.Methods: The proposed solution is a semiautomatic interface which translates these data into a relational database on a daily basis, interprets the requests coming from external centers and produces reports. The prospective to use this tool for several centers indicates to us the need to choose an HL7 output for the interface.Results: A prototype version of this program was installed in February 2004. In this period, routine work has been recorded with an average of 6.5 samples per day, with a maximum of 23 samples. Moreover, historical data from 1998 has been translated. The main source of errors in these data was due to patient identification problems with an average occurrence of 4.06% in the virology section and of 4.16% in the microbiological division.Conclusions: A complete reorganization of the system would be desirable but at the moment it is not realistic because of obvious budget problems. The proposed approach, mainly the HL7 interface, seems to be a reasonable compromise.
Keywords: Microbiological data sharing; transplant patient treatment; medical data standardization